THE FARMERS MOTIVATION IN BALI COW CULTIVATION AT PARIGI OF MUNA DISTRICT - Ningsih, Sitti Rahmiati; Sani, Laode Arsad; Abadi, Musram (Pascasarjana Universitas Sulawesi Tenggara, 2020)
Farmer's motivation is essential for developing livestock farming businesses, especially theBali cattle business in Sub-district Parigi, Muna Regency. This study aimed to determine themaintenance system and motivation for raising Bali cattle in Sub-district Parigi, MunaRegency. The course's location was determined intentionally (purposive sampling) that isSub-district Parigi based on the consideration that it had the highest population of Bali cattleamong the other sub-districts in Muna, which was 6,338 individuals. The determination ofbreeders as respondents was carried out randomly in Parigi, Warambe, Kolasa, andWasolangka. Each village was taken as many as 15 respondents, so that a total of 60 people.This study's variables were livestock raising systems, breeding motivation, includingeconomic stimulus, social status motivation, environmental motivation, and productionmotivation. The results showed that the raising system of Bali cattle in Sub-district Parigi wascommonly conducted by using traditional or extensive (46.7%) methods. The highestmotivation for raising Bali cattle in Parigi District was economic motivation (70%), whileother reasons such as environment, production, and social status were medium and lowmotivation categories.